Genotype-environment interaction for age at first calving in buffaloes, using the reaction norm model - Freitas, Gabriela Rodrigues; Alejandro Hurtado-Lugo, Naudin; Abreu dos Santos, Daniel Jordan de [UNESP]; Aspilcueta Borquis, Rusbel Raul; Pegolo, Newton Tamassia; Tonhati, Humberto [UNESP]; Araujo Neto, Francisco Ribeiro de (Wiley-Blackwell, 2019)
Contents The objective of this study was to evaluate the genotype-environment interaction effect on age at first calving in buffaloes. The records were analysed using two approaches: (a) standard animal model and (b) reaction norm model. For the reaction norm analysis, two environmental gradients were formed, using age of first calving or milk yield group contemporary average. The results showed differences in the heritability estimates when using the two approaches. The reaction norm model indicated high heritability in more favourable environments and low magnitude genetic correlations between extreme environments. Based on our findings, we verified the significance of the genotype-environment interaction effect on age at first calving in buffaloes.
Keywords: economic traits; environmental response; reproduction